1978
DOI: 10.18174/njas.v26i2.17093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leaf removal on yield components in sunflower.

Abstract: In a study of the relationship between leaf apparatus and yield in sunflower, the Rumanian hybrid HS 18 and the French hybrid INRA 4701 were subjected to a variety of leaf removal treatments. These treatments differed both in the number and in the position of the leaves removed. The leaves were removed one at a time during the vegetative period in one series and all at once shortly before flowering in another. The effects of the various treatments on final plant ht., size of head, seed setting and different as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…Though not significant, it could be observed that higher levels of N, P, K and Cl were noted in the pruned palms compared to unpruned palms (Figure 6). This observation supports the earlier claims of Das Cupta (1972) and Pereira (1978) that when leaves are removed, the photosynthetic efficiency of the remaining leaves is improved. Likewise, Delting et al, (1979) and Heichel and Turner (1985) added that mobile nutrients such as N, S, K, and Cl as well as water become readily available to the remaining leaves.…”
Section: Effect Of Coconut Leaf Pruning Coffee Variety and Their Interaction On Leaf Nutrient Content Of Coconut And Coffeesupporting
confidence: 92%
“…Though not significant, it could be observed that higher levels of N, P, K and Cl were noted in the pruned palms compared to unpruned palms (Figure 6). This observation supports the earlier claims of Das Cupta (1972) and Pereira (1978) that when leaves are removed, the photosynthetic efficiency of the remaining leaves is improved. Likewise, Delting et al, (1979) and Heichel and Turner (1985) added that mobile nutrients such as N, S, K, and Cl as well as water become readily available to the remaining leaves.…”
Section: Effect Of Coconut Leaf Pruning Coffee Variety and Their Interaction On Leaf Nutrient Content Of Coconut And Coffeesupporting
confidence: 92%
“…Findings of this work supports earlier claims of workers that when leaves are removed, likely the photosyn-thetic efficiency of the remaining leaves are improved (Das Cupta, 1972;Pereira, 1978); mobile nutrients (e.g. N, S, K and Cl) and water becomes readily available to the remaining leaves.…”
Section: Effect Of Leaf Pruning On Copra Yieldsupporting
confidence: 88%
“…It was thought that these negative results were caused by the incorrect and incomplete application of the methods used in those researches. In some studies, all leaves in plant were removed [7][8][9], while 1/3 or 2/3 of leaves were removed in some other ones [9,10]. Or defoliation was carried out in the lower, middle, and upper leaves of the plants [11,12].…”
Section: Resultsmentioning
confidence: 99%